Upaya Bank Syariah Dalam Mengatasi Pembiayaan Bermasalah Pada Akad Murabahah - Dwi, Septy Rahma; N, Nurnasrina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Murabaha-based financing is one of the main instruments utilized by Islamic banks to support financing activities in the real sector. However, the implementation of this contract often faces challenges, especially related to the risk of non-performing financing or potential defaults. This article aims to explore strategies undertaken by Islamic banks in managing non-performing financing in murabahah contracts, while maintaining compliance with sharia principles and maintaining financial stability. Through a literature study approach, this research aims to identify the factors that cause such non-performing financing and understand the efforts of Islamic banks in overcoming non-performing financing in murabahah contracts. This research is expected to be useful in providing an explanation of the resolution of murabahah financing problems in Islamic banks and uncovering the various factors that cause the emergence of non-performing financing. The findings show that these measures contribute significantly to improving the effectiveness of handling non-performing financing as well as maintaining customer trust and the reputation of Islamic banks in the community.